La trilogie des Trois corps de Liu Cixin et le statut de la science-fiction en Chine contemporaine - Gwennaël Gaffric (ReS Futurae)
The recent success of Liu Cixin’s hard SF Three-Body (Santi 三体) trilogy (2006-2008) is symbolic of the important rise taken of the Chinese science fiction, both in China and in the rest of the World. This trilogy tells the story of the future invasion of the Earth by a belligerent extraterrestrial civilization with advanced technology and the way humans try to defend themselves begins with the Chinese Cultural Revolution and ends with the heat death of the universe. Huge bestseller, great critical success, soon adapted to a series of movies, the English translation of the first volume also won the Hugo Award for Best Novel in 2015. With the considerable success he achieved with this trilogy, Liu Cixin has become for the readers, critics and even supporters of Chinese soft power the standard-bearer of a new “era” of Chinese science fiction, called to promote the “Chinese dream” to the international community. In the light of the history of science fiction in China since 1949 and its political distortion, this present contribution aims to offer an examination of the conditions of production and reception of the Three Body trilogy in China and abroad and to try to understand the reasons for the critical, academic and even political passion that it arouses today.